Variants of the Circle of Willis as seen on magnetic resonance angiography and carotid siphon calcifications in community-dwelling older adults. Issue 3 (June 2022) - Del Brutto, Oscar H; Recalde, Bettsy Y.; Mera, Robertino M
Background and purpose: Information on the association between anatomical variants of the Circle of Willis (CoW) and intracranial atherosclerotic disease (ICAD) is limited and results are controversial. In this population-based study, we aimed to assess whether an incomplete CoW is associated with high calcium content in carotid siphons (a reliable biomarker of ICAD) in community-dwelling older adults of Amerindian ancestry. Methods: Individuals aged ≥60 years enrolled in the Three Villages Study received a head computed tomography (CT) and magnetic resonance angiogram (MRA) of intracranial vessels. The CoW was classified in complete or incomplete according to the presence or absence of one A1 segment of the anterior cerebral artery or one or both P1 segments of posterior cerebral arteries. Calcium content in carotid siphons was rated as low or high. A multivariate logistic model was fitted to assess the independent association between incompleteness of the CoW and high calcium content in carotid siphons, after adjusting for demographics and cardiovascular risk factors. Results: A total of 581 individuals were enrolled (mean age: 71 ± 8.4 years; 57% women). MRA revealed an incomplete CoW in 227 (39%) individuals, and high-resolution CT disclosed high calcium content in carotid siphons in 185 (32%). A risk factor logistic regression model showed no independent association between incompleteness of the CoW and high calcium content in carotid siphons (odds ratio: 0.91; 95% confidence interval: 0.62–1.34; p = 0.631). Conclusion: Study results disclosed no association between anatomical variants of the CoW and the presence of high calcium content in carotid siphons.